Molecular Pathogenesis, Immunopathogenesis and Novel Therapeutic Strategy Against COVID-19 - Chatterjee, Swapan K.; Saha, Snigdha; Munoz, Maria Nilda M. (Frontiers in Molecular Biosciences, 2020)
The coronavirus disease 2019 (COVID-19), is a highly contagious transmittable disease caused by a recently discovered coronavirus, pathogenic SARS-CoV-2. Followed by the emergence of highly pathogenic coronaviruses in 2003 SARS-CoV, in 2012 MERS-CoV, now in 2019 pathogenic SARS-CoV-2, is associated with a global “pandemic” situation. In humans, the effects of these viruses are correlated with viral pneumonia, severe respiratory tract infections. It is believed that interaction between ACE2 cell receptor and viral Spike protein mediates the coronavirus entry into human respiratory epithelial cells and establishes the host tropism. ACE2 receptor is highly expressed in airway epithelial cells. Along with viral-receptor interaction, proteolytic cleavability of S protein has been considered as the determinant of disease severity. Several studies highlight the occurrence of impaired host immune response and expression of excessive inflammatory response especially cytokines against viral infection. The mechanisms of SARS-CoV-2 induced acute lung injury are still undefined; however, the term cytokine storm has now been recognized to be closely associated with COVID-19. The levels of inflammatory mediators from cytokine storm cause damage to the host cells. In particular, the proinflammatory cytokine IL-6 appears to be the key mediator in the early phase of virus-receptor interaction; however, secreted IL-6 might not be representative of lung inflammation. Understanding the cellular, and molecular factors involved in immune dysregulation and the high virulence capacity of COVID-19 will help in potential targeted therapy against it. “Drug repurposing” and “molecular docking analysis” is considered as an attractive alternative approach in analyzing suitable drug candidates to combat SARS-CoV-2 infection. Globally, extensive research is in progress to discover a new vaccine for the novel COVID-19. Moreover, our review mainly focuses on the most state-of-the-art therapeutic approach mediated by “Mannose-binding lectin (MBL)”. One of the most significant molecules of innate immunity is MBL. It plays a major role in the activation of the complement system as an ante-antibody prior to the response of any particular antibody. Recombinant human MBL can be used as immunomodulators against SARS-CoV-2.